Autoimmune manifestations in human myelodysplasia: a positive correlation with interferon regulatory factor-1 (IRF-1) expression. Issue 5 (13th April 2004) - Giannouli, S; Tzoanopoulos, D; Ritis, K; Kartalis, G; Moutsopoulos, H M; Voulgarelis, M
Abstract : Background: Patients with myelodysplasia may have autoimmune manifestations (AIM). Interferon regulatory factor-1 (IRF-1) is a transcription factor involved in interferon signalling, leukaemogenesis, and the development of the immune system. Objectives: To determine whether IRF-1 is implicated in the pathophysiology of AIM in myelodysplasia. Methods: 14 patients with myelodysplasia were studied, seven with AIM and seven without. Five patients with vasculitis and seven normal subjects served as controls. The expression of IRF-1 was studied in bone marrow mononuclear cells taken from patients and controls, using a relative quantitative reverse transcriptase polymerase chain reaction. Results: A 10-fold reduction in full length IRF-1 mRNA was detected in the myelodysplasia patients without AIM compared with the normal controls. In contrast, the group with AIM had increased IRF-1 transcripts, to a level almost equal to that observed in patients with vasculitis and normal controls. Conclusions: Myelodysplasia patients without IRF-1 expression had a decreased incidence of AIM. Thus the absence of IRF-1 transcription factor appears to protect against the development of autoimmunity in myelodysplasia.